Difficult intubation of a patient with progressive multifocal leukoencephalopathy and muscle spasticity - A case report - Kim, Ji-Eun; Yang, Young-Kwon; Kwon, Mi-Young; Yun, Mi-jung; Kim, Gunn-Hee (Anesthesia and pain medicine (Korean society of anesthesiologists), 2018)
Progressive multifocal leukoencephalopathy (PML) is a demyelinating central nervous system disease characterized by neurological deficits, including cognitive impairment, altered mental status, and muscle spasticity. Preoperative evaluation and intraoperative airway management of the airway is difficult in patients with this disease. In this report, the authors describe a 62-year-old man with PML and spastic hemiparesis, who was scheduled for video-assisted thoracic bullectomy under general anesthesia. A preoperative airway evaluation, including Mallampati classification, could not be performed due to lack of patient cooperation. Additionally, the anesthesiologist did not perform diverse physical assessments of the airway or prepare an adequate airway management strategy. During induction of general anesthesia, difficulty with intubation was encountered because of limited mouth opening. This case emphasizes that anesthesiologists should have thorough knowledge of airway assessment and management strategies, and perform a comprehensive assessment to implement appropriate airway management in patients with this disease. KCI Citation Count: 0